A framework for for the analysis of determinants of social media acceptance in higher educational institutions of Pakistan - Soomro, Ali Raza; Chandio, Fida Hussain; Koondhar, M Yaqoob; Rind, M Malook; Shah, Asadullah (2015)
Social media is being considered an important source in the perspective of academic learning in the educational sector. The scope of learning through social media encompasses broadening the information sharing through collaborative approach with the help of web-based social networking sites as the means to enhance the knowledge of coworkers, colleagues and other mates. Due to large scale penetration of social media among youngsters, it is being perceived to be one of the futuristic approaches for next generation knowledge sharing and academic learning. On one hand, learning through social media has attained an important value in developed economics but on the other hand, real benefits and future implications have not been interpreted and realized in developing economics like Pakistan. Educational institutes in Pakistan need to evaluate and understand the importance and use of social networking for the sake of its valued role in academia. Although research communities in the developing countries are paying attention towards the development of this sector in academia but Pakistan still has to go a long way in this regard. The aim of the study is to explore the significant factors which are affecting the delayed acceptance and usage of social media for academic learning purpose. This research proposes an integrated framework including some widely accepted technology models such as Technology Acceptance Model (TAM) and Innovation Diffusion Theory (IDT) to determine significant factors.